(untitled) - Pekeur, Jade Chantel

Investigation of the contribution of oral bacterial microbiota to health and disease in a South African cohort. (Stellenbosch : Stellenbosch University, 2024)
Thesis (MSc)--Stellenbosch University, 2024.